Analisis Sistem Informasi Pelayanan Jasa In-House Training pada PT. Sigma Global Internasional Jakarta - Agus Hamdi (Bina Nusantara University, 2013)
One key to success is the company's strategy to improve performance in information systems that are reliable. Effective information is expected to help companies to do things related to the mechanism of decision-making quality, efficient management process, as well as effective communication and collaboration culture. PT Sigma Global International Jakarta is a private training and consulting services nationwide that provides consulting services in the aspects of customer satisfaction and do sales through creative and innovative work of all competent employees. To see and resolve the weaknesses that occur in the system in-house training services PT Sigma Global International Jakarta needs evaluation and analysis.